Z dziejów administracji państwa stanu wyjątkowego. Ustrój administracji publicznej na terenach byłego zaboru austriackiego u progu II Rzeczypospolitej - Kostrubiec, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
In the reborn Poland, in the territories of the three former partitions, the creation of Polish centres of administrative power and its structures took place in a different political and legal environment. The main purpose of this article is to present the specificity of the process of creating public administration structures and determining its organizational model in the territories of the former Austrian partition in the context of the reconstruction of the Polish country. The article focuses on the status and rules of organization of public administration introduced by the Polish Liquidation Committee, Interim Governing Committee of Eastern Galicia, the Governing Committee, the General Government Delegate of Galicia and the National Council of the Duchy of Cieszyn. The main thesis of the author of the article is the statement that at the time of creating public administration structures in the territories of the former Austrian partition, the duality principle of the government and self-government administration was no longer in use, transferring the responsibility of administering to the monocratic administration authorities.
Keywords: lokalna administracja; administracja publiczna na terytoriach byłego zaboru austriackiego; ewolucja lokalnej administracji; II Rzeczpospolita Polska